THE PLIGHT OF THE HOUSE-HELPS (DOMESTIC WORKERS) IN SELECTED ESTATES IN EASTLANDS AREA, NAIROBI COUNTY, KENYA - Nyaura, Jasper Edward; Ngugi, Margaret Njeri (PEOPLE: International Journal of Social Sciences, 2019)
In Kenya, households in the middle class suburbs have increasing involvement of house-helps who in most cases take care of household chores. Moreover house helps have borne the brunt of being among the least paid in the country. Therefore, this paper focused on the plight of the house-helps in selected estates in Eastlands in Nairobi County. More specifically, the study sought to: investigate the demographic characteristics of the house-helps; perceived socio-cultural factors influencing female house-help participation in domestic work; the perceived economic factors influencing female house-help involvement in domestic work and finally the causal challenges faced by the female house-helps. A descriptive research design was used in the study. Data was collected using the interview schedule, which was administered to women found in households in selected estates in Eastlands area in Nairobi. The study purposively targeted house-helps with the experience of three years and above. Simple random sampling technique was applied in picking the respondents in each Household. The sample size was 82. The salient findings of the study indicate that the house-helps faced hardship in their working environment. It is thus recommended that their plight should be addressed by all stakeholders more so the government so as to factor in the existing labour laws both nationally and internationally.